PERBEDAAN TINGKAT HEALTH LITERACY DALAM BIDANG KESEHATAN REPRODUKSI WANITA PADA MAHASISWA DAN MAHASISWI UNIVERSITAS MATARAM TAHUN ANGKATAN 2010 DARI FAKULTAS KEDOKTERAN DAN NON-FAKULTAS KEDOKTERAN - Yuliyanti, Arrum Chyntia; I., Siti Farida; Santyowibowo, T.; Gerudug, I Komang (Jurnal Kedokteran, 2014)
Background: The ability of individuals to gain access to, understand and use health information in ways which promote and maintain good health is determined by skills called health literacy.Education is one of the factors that affect a person’s health literacy skills. Health literacy has large impact on people’s health, particularly in the field of women's reproductive health. Data on the health literacy skills in the field of women’s reproductive health in Indonesia was not clear. This study was aimed to determine the difference in women's reproductive health literacy between medical students and non-medical students of Mataram University academic year of 2010. Methods: This study design was a descriptive analytic study. A cross-sectional study was performed using consecutive sampling technique. The participants chosen were students of the Faculty of Medicine, Faculty of Economics, and Faculty of Law of Mataram University academic year of 2010who met inclusion criteria.A validity and reliability tested self-administered questionnaire was used.The data were analyzed by using descriptive analysisand nonparametric Kruskal-Wallis test and Mann-Whitney test, withconfidence interval for mean was 95%. Results: Health literacy score among women participants was higher than men. Men participants had more mistake in answering either text or document questions.Women’s reproductive health literacy among students of the Faculty of Medicine was very good, Faculty of Economics was good, and the Faculty of Law was moderate. Significance value obtained based on Kruskal-Wallis test was p